Caracterização bioquímica e funcional da ação da peptidase de Thermomucor indicae-seudaticae N31 sobre a caseína - Geraldes, Fernanda Martucci [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Peptidase enzymes are responsible for catalyze the cleavage of peptide bonds of other proteins. These enzymes present great importance, therefore, are used in several industrial segments, since the food industry even in the processing of leather and formulations of medicinal products. One major application of peptidases is in the dairy industry for cheese production, which initially involves clotting of milk caseins by the action of coagulant proteolytic enzymes being rennin the main one. Microbial rennet-like milk-clotting enzymes are aspartic proteinases that catalyze milk coagulation, substituting calf rennet. In previous study it was isolated a thermophilic fungus Thermomucor indicae-seudaticae N31 that produced on Solid State Fermentation (SSF), a peptidase with capacity to hydrolyses the k-casein of milk and produce good quality curd. However its functional characterization and specificity of action is not clear yet. Thus, in this study we continued the investigation of structure and action of this enzyme coagulant. Was carried out the monitoring of enzymatic hydrolysis of casein by high performance liquid chromatography-reverse phase, was analyzed the specificity of primary peptidase using substrate of fluorescence resonance energy transfer (FRET) peptide series Abz-LSFMAIQ-EDDnp and determined the primary sequence of the protein by mass spectrometry. Monitoring the enzymatic hydrolysis of casein by high performance liquid chromatography-reverse phase showed that the crude extract Thermomucor indicae-seudaticae N31 shows high similarity with commercial enzymes brands Bela-Vista and Chr-Hansen obtained from fungi Rhizomucor miehei and Aspergillus niger, respectively. The analysis of primary peptidase specificity demonstrated high specificity and affinity for the synthetic substrate. The determination of the cleavage site showed 46% hydrolysis of the bond between the amino acids phenylalanine and methionine and 54% between alanine ...

Peptidases são enzimas responsáveis por realizar a clivagem de ligações peptídicas de outras proteínas e peptídeos. Essas enzimas apresentam grande importância, pois são utilizadas em vários segmentos industriais, desde a indústria alimentícia até mesmo no processamento de couro e pele e formulações de medicamentos. Uma das principais aplicações das peptidases é nos laticínios, na produção de queijo, que inicialmente envolve a coagulação das caseínas do leite pela ação de enzimas proteolíticas coagulantes, sendo a renina a principal delas. Enzimas microbianas coagulantes de leite são peptidases aspárticas que catalisam a coagulação do leite, substituindo o coalho de vitelo. Em trabalhos anteriores foi isolado o fungo termofílico Thermomucor indicae-seudaticae N31 que produziu em fermentação em estado sólido (FES), uma peptidase com capacidade de hidrolisar a κ-caseína do leite e produzir coágulo de boa qualidade. Entretanto, sua caracterização funcional e especificidade de ação ainda não estão claras. Assim, neste estudo, deu-se continuidade à investigação de estrutura e ação desta enzima coagulante. Foi realizado o monitoramento da hidrólise enzimática da caseína por cromatografia líquida de alta eficiência, foi feita análise da especificidade primária da peptidase utilizando substrato de fluorescência da série Abz-LSFMAIQ-EDDnp e foi determinada a sequência primária da proteína por espectrometria de massas. O monitoramento da hidrólise enzimática da caseína por cromatografia líquida de alta eficiência mostrou que o perfil do extrato bruto de Thermomucor indicae-seudaticae N31 apresenta alta similaridade com as enzimas comerciais das marcas Bela-Vista e Chr-Hansen obtidas dos fungos Rhizomucor miehei e Aspergillus niger, respectivamente. A análise de especificidade primária da peptidase demonstrou alta especificidade e afinidade pelo substrato sintético. A determinação do ...
Keywords: Microbiologia industrial; Enzimas de fungos - Aplicações industriais; Fungos termofilicos; Derivados do leite - Processamento; Cinetica de enzimas; Fermentação em estado sólido; Caseina; Hidrolise; Enzimas proteoliticas; Industrial microbiology